Tomboy And Feminine Representations: Gender Standards in Children's Literature Written by Children in The Comics Next G - Tegar Prasetyo; Novi Siti Kussuji Indrastuti (Universitas Cokroaminoto Palopo, 2026)
This study has two primary objectives. First, to analyze how the representations of tomboy and feminine characters are constructed in Komik Next G. Second, to examine whether this representation reproduces conventional gender stereotypes or offers alternative meanings of femininity. The method employed is qualitative descriptive using Stuart Hall's representation framework (encoding, representation, decoding). Data sources consist of verbal and visual elements from Komik Next G, collected through non-participatory observation and note-taking techniques on story panels. Data analysis involved four stages: identifying visual/verbal signs, classifying gender expressions, interpreting cultural meanings, and a systematic comparison utilizing data reduction, display, and conclusion drawing. The results indicate that Komik Next G predominantly reproduces conventional binary gender standards. Femininity is constructed as a natural, ideal norm through visual and verbal attributes and operates through the hegemony of friendship and social rewards. The tomboy identity, while predominantly framed as a deviation requiring correction, is not entirely devoid of agency: the character demonstrates moments of active resistance, autonomous spatial negotiation, and an ambivalent inner desire that complicate a reading of pure passivity. However, this agency is ultimately subjugated and channeled toward a normative resolution, with any remaining resistance reduced to a tolerated “mischief” that leaves the feminine visual standard intact, children as text producers have deeply internalized hegemonic gender norms, underscoring the urgency for critical guidance in children’s literacy programs to encourage more inclusive gender narratives.